Peningkatan Pengetahuan pada Lanjut Usia mengenai Penyakit Stroke di Posyandu Lanjut Usia Kelurahan Sukodadi Kecamatan Sukarame Palembang - Yofa Anggriani Utama; Sutrisari Sabrina Nainggolan (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Stroke is a neurologic disease that accurs because the blood supply to the bloodsupply to the brain is distrurbed or blocked, many risk factors can cause a stroke, one of with is diabetes melitus, hypertension, high cholesterol levels. Patients who suffer from stroke will certainly experince various probematics, limitations and obstacles at all levels including body structure, body fuctions, activities and participation in the enviroment and daily life. The purpose of this community service activity is to increase public knowledge about stroke. Methods the implementation of this service is carried out off line for the elderly at the elderly posyandu melati. This activity was attended by 21 participants. Based on the results of the activity, it was found that the level of knowlegde befero being given health counseling was 15 people (71,5%), participants had poor knowlegde about stroke. After being given health education, there was an increase in knowledge as many 14 people (67%) of comunity service participants had goog knowledge about stroke.